Synthesis, structure and characterisation of rac and meso-ansa-bridged permethylindenyl cobalt complexes - Ransom, P; Ashley, A; Thompson, A; O'Hare, D (2009)
Disodium ethylene-bis-hexamethylindenyl, {(C9Me6)2C2H4}Na2 (EBI*Na2), has been prepared in good yield by the reaction of lithium heptamethylindenyl with cyanogen bromide followed by treatment with sodium naphthalenide. EBI*Na2 reacts with anhydrous Co(acac)2 to give a mixture of rac and meso-ethylene-bis-hexamethylindenyl cobalt(II) (EBI*Co). The isomers can be separated by fractional crystallisation and the rac-isomer has been structurally characterised. Oxidation of the reaction mixture yields both rac and meso-ethylene-bis-hexamethylindenyl cobalt(III) which have both been structurally characterised. © 2008 Elsevier B.V. All rights reserved.